The integrated theory of development assistance - an initial statement - Budhoo, Davison L. (UWI. ISER MonaJM, 1973)
Proposes a new aid epistemology that provides guidelines on processes for disbursing development assistance to ensure its effective use. Identifies areas of responsibility in aid administration for donors and recipients. Makes a classification of past and current operations of the World Bank.